VD_FINDINFO Jug / 2018 / 261 vom 20. September 2019 - VD Tribunal cantonal (2019)
PERTE DE GAIN, TORT MORAL, DOMMAGE INDIRECT, HONORAIRES, FRAIS DE FORMATION | 422 CO, 46 CO, 47 CO, 49 CO, 291 CPC, 58 LCR, 62 LCR, 65 LCR